Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 13, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 13, 1930. Augustus Brandegee's optimism over the burying of the hatchet between Hartford and New Haven in 1880 was not only vindicated in the state election, but it was prophetic. Hawley had been a candidate for senator upon several occasions. Once he had won the caucus nomination, only to have a party bolt, partly engineered from New Haven, deprive him of an honor justly his. It was, therefore, perhaps an even greater satisfaction to him when the republican legislative caucus in January 1881, nominated Hawley for United States senator unanimously by acclamation. It was the first time in the history of the republican party that had happened. It was peculiarly appropriate that it was Hawley, in whose office the Connecticut republican party was founded, who should be thus honored.
1 electronic record. Scanned newspaper article. 1 image scans. 862 KB (882,888 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 19.6 MB (20,592,569 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers